THE EFFECTIVENESS OF WET CUPPING THERAPY AGAINST MENSTRUAL PAIN (DYSMENORRHEA) ON COLLEGE STUDENT NURSING OF STIKES SURYA GLOBAL YOGYAKARTA - Andi, Sukma; Setyawan, Aris (International Islamic Medicine Forum, 2022)
Dysmenorrhea is a physical disorder during menstruation that causes decreased activity, enthusiasm, and attention to learning. The complaint consists of pain, headaches, and fatigue. Dysmenorrhea needs to be overcome with the wet cupping therapy. The study aims to determine Wet Cupping Therapy's effectiveness on menstrual pain (dysmenorrhea) in nursing students. This study used a pre-experimental research design with a pre-post test design model with 15 respondents. The instrument in this study used a Numeric Rating Scale for pain measurement. The research analysis used a normality test using Shapiro-Wilk and Wilcoxon test analysis. The analysis results show that there is a significant difference with a p-value of 0.001. So it can be concluded that wet cupping (cupping) effectively reduces the intensity of menstrual pain (dysmenorrhea ) in nursing students.